2002
DOI: 10.1075/jgl.3.08ter
|View full text |Cite
|
Sign up to set email alerts
|

Politeness and formulaicity: Evidence from Cypriot Greek

Abstract: In Brown and Levinson’s politeness theory, the degree of indirectness of an utterance is presumed to be commensurate with the sum of the variables of Distance, Power and Ranking of an imposition. This claim was tested with reference to a corpus of spontaneous requests from Cypriot Greek. It emerged that, rather than motivating the choice of a ‘generic’ politeness strategy corresponding to a certain degree of indirectness, particular combinations of values of extra-linguistic variables (such as sex, age and soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
6

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 4 publications
0
31
0
6
Order By: Relevance
“…To Chaemsaithong (2012), choices of conventional forms over other available options may be interpreted as instances of politeness. Similarly, Terkourafi (2002) shows that polite discourse involves formulaic language to a significant extent. Both authors imply here the connection between conventionalisation and politeness directed at others.…”
Section: Conventionalisation As Other-politeness?mentioning
confidence: 96%
“…To Chaemsaithong (2012), choices of conventional forms over other available options may be interpreted as instances of politeness. Similarly, Terkourafi (2002) shows that polite discourse involves formulaic language to a significant extent. Both authors imply here the connection between conventionalisation and politeness directed at others.…”
Section: Conventionalisation As Other-politeness?mentioning
confidence: 96%
“…It is particularly interesting to note that the strong presence of positive politeness strategies in Greek conversational narratives reflects Greek society's general orientation towards positive politeness, that is, the preference for building relations of camaraderie and familiarity in personal encounters (see among others, Sifianou, 1992;Pavlidou, 1994;Hirschon, 2001;Tzanne, 2001;Terkourafi, 2002;Makri-Tsilipakou, 2003). Hence, it seems that narrative in Greek society may be considered a conversational practice for cultivating social relations (see Archakis and Tzanne, 2009).…”
Section: The Impact Of the Narrative World On Narrative Interactionmentioning
confidence: 98%
“…"This finding is" as Terkourafi points out, "not new", since "[p]revious research has shown that hints (i.e. off-record indirectness) are not universally or uncontroversially perceived as polite" (Terkourafi 2011a: 2862, see Blum-Kulka 1987: 136, Holtgraves and Yang 1990: 724, Weizman 1993: 125, Turner 1996: 5-6, Marquez Reiter 2000and Terkourafi 2002. Sometimes people speak indirectly due to face concerns, which may or may not include considerations about ignorability of interpretation, while other times the venue of indirect speech are chosen because it enables the speaker to deny that he meant what he actually did mean.…”
Section: Indirect Speech and Deniabilitymentioning
confidence: 99%